2022
DOI: 10.3390/ijerph191811795
|View full text |Cite
|
Sign up to set email alerts
|

Postvention as Prevention: Coping with Loss at School

Abstract: Many Pre-K through grade 12 (PK-12) students have experienced traumatic events throughout the pandemic in a myriad of ways including the death of family members and peers, loss of social interaction and increased violence at home. The consequences can be traumatic and manifest themselves in fear, anxiety, anger, isolation, and loneliness. Too often this leads to depression, anxiety, grief, substance use disorders, post-traumatic stress disorder, suicidal ideation and even suicides. This study assesses the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The authors found that homeroom teachers suffered more from complicated grief and post-traumatic stress disorder (PTSD) compared to psychologists and counsellors and, as such, should receive more preparatory training. Additionally, in the context of schools, Khalid and colleagues [ 21 ] found encouraging results from a training program that increased preparedness and skills in school staff to respond to student suicides. Rivant and colleagues [ 22 ] focused on suicide bereavement among ethnic minority groups.…”
Section: Impact Of Suicide and Adverse Grief Reactionsmentioning
confidence: 99%
“…The authors found that homeroom teachers suffered more from complicated grief and post-traumatic stress disorder (PTSD) compared to psychologists and counsellors and, as such, should receive more preparatory training. Additionally, in the context of schools, Khalid and colleagues [ 21 ] found encouraging results from a training program that increased preparedness and skills in school staff to respond to student suicides. Rivant and colleagues [ 22 ] focused on suicide bereavement among ethnic minority groups.…”
Section: Impact Of Suicide and Adverse Grief Reactionsmentioning
confidence: 99%